2018
DOI: 10.1051/matecconf/201824003016
|View full text |Cite
|
Sign up to set email alerts
|

Viscous dissipation effect on laminar forced convection in a circular duct with adiabatic walls - preliminary numerical investigation

Abstract: In this work, an analysis of laminar forced convection in a pipe with heated and adiabatic walls for a Newtonian fluid with constant properties is performed by taking the viscous dissipation into account when the axial heat conduction in the fluid is neglected. The Nusselt number versus the Brinkmann, which is based on the total wall heat flux density, have been investigated. In order to determine the temperature field, an analytical solution describing the velocity field in the pipe was used, while the energy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…They showed that the effect of viscous dissipation could not be neglected when the wall temperature was uniform. For in-tube thermal conditions, Chaudhuri and Das [6] by using semi-analytical method, Teleszewski [7] for a tube with adiabatic wall and Newtonian fluid, Daghighi and Norouzi [8], and Dang [9] for a constant temperature wall condition, have been studied the effect of viscous dissipation in the thermal input region of a tube.…”
Section: Introductionmentioning
confidence: 99%
“…They showed that the effect of viscous dissipation could not be neglected when the wall temperature was uniform. For in-tube thermal conditions, Chaudhuri and Das [6] by using semi-analytical method, Teleszewski [7] for a tube with adiabatic wall and Newtonian fluid, Daghighi and Norouzi [8], and Dang [9] for a constant temperature wall condition, have been studied the effect of viscous dissipation in the thermal input region of a tube.…”
Section: Introductionmentioning
confidence: 99%